Diseño de un proceso contable, para mejorar la gestión en la Cooperativa de Productores Agropecuarios Emprendedores Bolivarenses COPEMBO primero de mayo cantón Guaranda, provincia Bolívar año 2019 - Chimborazo Quicaliquin, Betty Piedad (2020)
This research work focuses on the realization of an agricultural accounting process for the Cooperativa de Agropecuarios Emprendedores Bolivarenses, the main activity is the sale of agricultural products, potatoes, beans, corn, carrots, began its activities with 28 members who to date, the 87 members make up and giving the accounting records of the movements in an empirical way, they would not have a real record and control in their operations, therefore they do not have the knowledge of the financial situation in which they are The cooperative The development of this research work was the methodology, inductive, scientific, being the deductive modality that predominates in the present development through the instruments with surveys, interviews could establish the diagnosis of the current situation of the cooperative. With the Design of the agricultural accounting process of the year 2019, it was possible to design an accounting process from the register of operations, the account plan, the financial statements, which improves the quality of financial information, help you to optimize of resources and reflects the reality of the entity for its respective decision making futures.